Optimization Of Potassium Extraction Method From Corncob Waste (Zea Mays L.) Using Aquadest - Zuhairiah Nasution; Nora Susanti; Predy Fernandes Sihaloho (Universitas Negeri Medan, 2025)
The purpose of this study was to determine the optimal extraction method of potassium from corn cobs in semibatch and batch. In this research, semibatch maceration is a leaching process used to obtain the time needed for the solvent to absorb alkali in corn cob ash. While the batch system maceration is a leaching process used to obtain the amount of time needed for the solvent to reach saturation point. Data collection techniques in this research are: sample preparation and drying of corn cobs, corn cobs pyrolysis, semibatch and batch maceration of corn cobs ash, and determination of alkali content by titration method. From the results, it can be concluded that corn cobss have the potential to be used as a source of alkali because the potassium (K) content in corn cob ash is 25.78%. The moisture content and yield of corn cob ash were 77.5% and 17%, respectively. The saturated solvent time for semibatch maceration was 3.5 days, while for batch maceration it was 12 days. Where at consecutive ratios of 1 gram/25 mL; 2 grams/25 mL; 3 grams/25 mL; and 4 grams/25 mL each had concentration values that still increased from 0.112 N to 0.9672 N; 0.223 N to 3.2364 N; 0.3348 N to 2.0646 N; and 0.558N to 3.6828 N. The highest alkali yield was obtained at a corn cob ash/solvent ratio of 1 gram/25 mL, which was 20.15%.